Formation of hydroxyapatite on bioglass in physiological solutions - Ng, Edwin Zhi Yong. (2010)
The formation of hydroxyapatite on bioactive glass was investigated by the immersion of bioactive glass in a medium known as Dulbecco's Modified Eagle Medium for a period of 17 days. The bioactive glasses were immersed for different periods of time and subjected to characterization techniques like Raman Spectroscopy and Field Emission Scanning Electron Microscope. Raman mapping of bioglass and mesoporous bioglass samples were carried out and the images were analysed by MATLAB programme. Singular value decomposition and Band Target Entropy Minimization analysis were then used to extract the pure component spectra present in each of the samples to determine the components present in the sample. This technique can be used to identify the presence of hydroxyapatite and thus confirm the formation of hydroxyapatite on bioactive glass.